PEMANFAATAN EKSTRAK ETANOL 70% KULIT JERUK SIAM KINTAMANI (Citrus nobilis L.) SEBAGAI BAHAN AKTIF PADA SEDIAAN LOTION ANTIOKSIDAN - Indraswari, Putu Ika Indah; Marangyana, I Gede Bagus Indra (Fakultas Farmasi UMI, 2024)
Kintamani Siam orange (Citrus nobilis L.) is the most dominant orange and has been successfully cultivated in Bali. Kintamani Siam orange peel can be used as a source of natural antioxidants. Antioxidants are substances needed by the body to neutralize free radicals and prevent damage caused by free radicals. This study aims to determine the comparison of antioxidant activity in 70% ethanol extract of Kintamani Siam orange peel through optimization of extraction methods: soxhletation and digestion, then optimizing the lotion formula with 3 comparisons of extract concentrations (2.5%, 5%, 7.5%). The next stage is to compare the physical and chemical properties of the lotion and the antioxidant activity it has. Based on the antioxidant activity test of 70% ethanol extract of Kintamani Siam orange peel, it shows that the extract from the digestion extraction results has antioxidant activity with a strong category. Then the test of the lotion: organoleptic tests, adhesion, spreadability, pH, and viscosity of the lotion preparation, showed that all formulas met all preparation requirements. Meanwhile, for the antioxidant activity test, the results showed that the lotion formula 3 preparation had the highest antioxidant activity with an IC50 of 138.52, which is in the medium category. It can be concluded that the lotion formula 3 preparation is the most optimal formula after the extract is formulated in the form of a antioxidant lotion.